Frailty assessment can predict textbook outcomes in senior adults after minimally invasive colorectal cancer surgery. Issue 3 (March 2023) - Taffurelli, Giovanni; Montroni, Isacco; Ghignone, Federico; Zattoni, Davide; Garutti, Anna; Di Candido, Francesca; Mazzotti, Federico; Frascaroli, Giacomo; Tamberi, Stefano; Ugolini, Giampaolo
Abstract: Aim: Colorectal cancer (CRC) surgery can be associated with suboptimal outcomes in older patients. The aim was to identify the correlation between frailty and surgical variables with the achievement of Textbook Outcome (TO), a composite measure of the ideal postoperative course, by older patients with CRC. Method: All consecutive patients ≥70years who underwent elective CRC-surgery between January 2017 and November 2021 were analyzed from a prospective database. To obtain a TO, all the following must be achieved: 90-day survival, Clavien-Dindo (CD) < 3, no reintervention, no readmission, no discharge to rehabilitation facility, no changes in the living situation and length of stay (LOS) ≤5days/≤14days for colon and rectal surgery respectively. Frailty and surgical variables were related to the achievement of TO. Results: Four-hundred-twenty-one consecutive patients had surgery (97.7% minimally invasive), 24.9% for rectal cancer, median age 80 years (range 70–92), median LOS of 4 days (range 1–96). Overall, 288/421 patients (68.4%) achieved a TO . CD 3–4 complications rate was 6.4%, 90-day mortality rate was 2.9%. At univariate analysis, frailty and surgical variables (ileostomy creation, p = 0.045) were related to. However, multivariate analysis showed that only frailty measures such as flemish Triage Risk Screening Tool≥2 (OR 1.97, 95%CI: 1.23–3.16; p = 0.005); Charlson Index>6 (OR 1.61, 95%CI: 1.03–2.51; p = 0.036) or Timed-Up-and-Go>20 s (OR 2.06, 95%CI: 1.01–4.19; p = 0.048) independently predicted an increased risk of not achieving a TO. Conclusion: The association between frailty and comprehensive surgical outcomes offers objective data for guiding family counseling, managing expectations and discussing the possible loss of independence with patients and caregivers.